Effect of Ni Addition on the Morphology and Microstructure of Both Conventional Cast and Melt-Spun of Al–Si–Fe–Nb (at wt%) Alloy - Kilicaslan, M. Fatih; Altaib, Salaheddin Salem; Vurdu, Can Doğan (Springer Science and Business Media LLC, 2019)
In this project the morphology and microstructure of both conventional cast and melt spun of Al–20Si–9Fe–1.2Nb and Al–20Si–9Fe–1.2Nb–6Ni (at wt%) alloys were investigated. Therefore, in order to study the effect of added Ni on the morphology characteristics of the above-mentioned alloy, the resulting conventional cast and ribbons of Al–20Si–9Fe–1.2Nb and Al–20Si–9Fe–1.2Nb–6Ni alloys were synthesized and analysed using OM optical microscopy, X-ray diffraction, SEM scanning electron microscopy together with EDS energy dispersive spectroscopy. Observations exhibit that, XRD patterns of Al–Si–Fe–Nb and Al–Si–Fe–Nb–Ni ribbons revealed the peaks of only α-Al phase. Therefore, after adding of 6 wt% Ni, peaks of α-Al were shifted to the relatively lower angles with a very weak intensity. Furthermore, 6 wt% Ni addition causes homogeneously scattered colonies (size range 5 –25 μm) which contain fine spherical (primary Si and δ-Al4(FeNiNb)Si2 phases) particles in the α-Al dendrite of rapidly solidified Al–20Si–9Fe–1.2Nb alloy, the size of spherical particles were found to be in the range of 100 nm–1 μm.